2018
DOI: 10.1152/jn.00737.2017
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens core medium spiny neuron electrophysiological properties and partner preference behavior in the adult male prairie vole, Microtus ochrogaster

Abstract: Medium spiny neurons (MSNs) in the nucleus accumbens have long been implicated in the neurobiological mechanisms that underlie numerous social and motivated behaviors as studied in rodents such as rats. Recently, the prairie vole has emerged as an important model animal for studying social behaviors, particularly regarding monogamy because of its ability to form pair bonds. However, to our knowledge, no study has assessed intrinsic vole MSN electrophysiological properties or tested how these properties vary wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
3
13
0
Order By: Relevance
“…D2-MSNs of NAc core, as well as dorsal striatum, also display enhanced intrinsic excitability (Ade et al, 2008;Cepeda et al, 2008;Chan et al, 2012;Chuhma et al, 2011;Gertler et al, 2008;Kreitzer & Malenka, 2007;Ma et al, 2013;Pascoli et al, 2014;Willett et al, 2018). Thus, the smaller mitochondria observed in D2 MSNs may represent reduced fusion as addressed above.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…D2-MSNs of NAc core, as well as dorsal striatum, also display enhanced intrinsic excitability (Ade et al, 2008;Cepeda et al, 2008;Chan et al, 2012;Chuhma et al, 2011;Gertler et al, 2008;Kreitzer & Malenka, 2007;Ma et al, 2013;Pascoli et al, 2014;Willett et al, 2018). Thus, the smaller mitochondria observed in D2 MSNs may represent reduced fusion as addressed above.…”
Section: Discussionmentioning
confidence: 93%
“…D2-MSNs display increased sEPSC frequency in NAc core and shell (Ma et al, 2013); however, another study examining NAc MSN subtypes in prepubertal mice demonstrated reduced mEPSC frequency in D2-MSNs in NAc core (Willett et al, 2018). D2-MSNs display increased sEPSC frequency in NAc core and shell (Ma et al, 2013); however, another study examining NAc MSN subtypes in prepubertal mice demonstrated reduced mEPSC frequency in D2-MSNs in NAc core (Willett et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations